2019
DOI: 10.1063/1.5088674
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast excited state intramolecular proton/charge transfers in novel NIR-emitting molecules

Abstract: The unusual large bathochromic shift from a novel near-infrared (NIR)-emitting molecule, 2-[3-(benzo[d]thiazol-2-yl)-2-hydroxy-5-methylstyr-yl]-3-ehtylbenzo[d]thiazol-3-ium iodide (named cyanine 1) with combination of intramolecular charge transfer (ICT) and intramolecular proton transfer (IPT) process in one molecular framework, is systematically investigated using ultrafast transient absorption (TA) spectroscopy and quantum chemical calculations. In order to understand the synergetic coupling effect of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…So far, tremendous efforts have been invested to investigate O–H-type ESIPT molecules with a strong intramolecular hydrogen bond, ,,,, while limited N–H-type ESIPT molecules have been reported owing to their relatively weak intramolecular hydrogen bond. , As one of the most fundamental and significant biological and chemical reactions, the N–H-type ESIPT reaction deserves more in-depth investigations. In our previous work, we synthesized a series of seven-membered ring pyrrole-indole intramolecular hydrogen bond systems, including 2-(5-(1 H -pyrrol-2-yl)-3 H -pyrrolizin-6-yl)-3,3-dimethyl-3 H -benzo­[ g ]­indole ( g -PPDBI ) and 2-(5-(1 H -pyrrol-2-yl)­3 H -pyrrolizin-6-yl)-1,1-dimethyl-1 H -benzo­[ e ]­indole ( e -PPDBI ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, tremendous efforts have been invested to investigate O–H-type ESIPT molecules with a strong intramolecular hydrogen bond, ,,,, while limited N–H-type ESIPT molecules have been reported owing to their relatively weak intramolecular hydrogen bond. , As one of the most fundamental and significant biological and chemical reactions, the N–H-type ESIPT reaction deserves more in-depth investigations. In our previous work, we synthesized a series of seven-membered ring pyrrole-indole intramolecular hydrogen bond systems, including 2-(5-(1 H -pyrrol-2-yl)-3 H -pyrrolizin-6-yl)-3,3-dimethyl-3 H -benzo­[ g ]­indole ( g -PPDBI ) and 2-(5-(1 H -pyrrol-2-yl)­3 H -pyrrolizin-6-yl)-1,1-dimethyl-1 H -benzo­[ e ]­indole ( e -PPDBI ).…”
Section: Introductionmentioning
confidence: 99%
“…In a collaborated effort, study from Guo et al further revealed the details of the photophysical process, showing the fluorescence lifetime of 1.75 ns for 8 in CH 3 CN. 14 These findings consistently indicate that the ESIPT is a rapid process. Although this class of new fluorescent dyes have strong donor–acceptor interaction in the excited state, as illustrated in 6b , they exhibit reasonably high fluorescence quantum yields (φ fl ≈ 0.20–0.35), which opens the possibility for various applications.…”
Section: Esipt-based Fluorescent Probes and Their Applicationsmentioning
confidence: 52%
“…The TA spectra at different time delays are presented exemplarily for toluene in Figure 2 and for other solvents in the Supporting Information (Figure S2). The lifetimes of TA signals were extracted by employing global analysis using a sequential model (Figure S3) [15] with two decay components τ 1 and τ 2 (E*) (Table 3). The obtained TA spectra for all three compounds in toluene, CHCl 3 , MeCN, and DMSO are similar to each other and do not show any significant spectral shape changes depending on substituent or solvent parameters.…”
Section: Compoundmentioning
confidence: 99%